2011
DOI: 10.5101/nbe.v3i4.p227-231
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimer-Functionalized Multi-walled Carbon Nanotubes Exhibit Dual-Phase Regulation to Exposed Murine Embryonic Stem Cells

Abstract: Herein we reported the effects of generation 5 polyamidoamine dendrimer-functionalized fluorescent multi-walled carbon nanotubes(dMNTs) on mice embryonic stem cell line CCE. The dMNTs were prepared and characterized, and incubated with murine embryonic stem cell CCE cells(ES) for 1 to 5 day. These ES cells were observed by fluorescent microscopy, and were analyzed by flow cytometer and MTT. Results showed that the dendrimerfunctionalized fluorescent multi-walled carbon nanotubes were successfully synthesized, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Effects of RGD-GNR-MWNT nanoprobes on viability of MGC803 and GES-1 cells were analyzed using Cell Counting Kit-8 (CCK8) assay [ 23 ]. MGC803 and GES-1 cells were cultured in a 96-well microplate at the concentration of 5,000 cells per well and incubated in a humidified 5% CO 2 balanced air incubator at 37°C for 24 h. Except for control wells, the remaining wells were added into the medium with RGD-GNR-MWNT nanoprobes.…”
Section: Methodsmentioning
confidence: 99%
“…Effects of RGD-GNR-MWNT nanoprobes on viability of MGC803 and GES-1 cells were analyzed using Cell Counting Kit-8 (CCK8) assay [ 23 ]. MGC803 and GES-1 cells were cultured in a 96-well microplate at the concentration of 5,000 cells per well and incubated in a humidified 5% CO 2 balanced air incubator at 37°C for 24 h. Except for control wells, the remaining wells were added into the medium with RGD-GNR-MWNT nanoprobes.…”
Section: Methodsmentioning
confidence: 99%
“…Up to date, many data showed that carbon nanotubes own cytotoxicity, and single walled carbon nanotubes exhibited stronger toxicity than multi-walled carbon nanotubes (MWCNTs) [10][11][12]. How to decrease carbon nanotubes' toxicity and enhance carbon nanotubes biocompatibility have become scientists' concerns, many methods have been tried [13].…”
Section: Introductionmentioning
confidence: 99%